Pretreatment with growth differentiation factor 15 augments cardioprotection by mesenchymal stem cells in myocardial infarction by improving their survival - Xinran Huang; Xiaoting Liang; Qian Han; Ying Shen; Jiaqi Chen; Ziqi Li; Jie Qiu; Xiaoyan Gao; Yimei Hong; Fang Lin; Weifeng Li; Xin Li; et al. (Stem Cell Research & Therapy)
Abstract Background The clinical application of mesenchymal stem cells (MSCs) in myocardial infarction (MI) is severely hampered by their poor survival. Pretreatment is a key strategy that has been adopted to promote their therapeutic efficacy. This study aimed to investigate the benefit of growth differentiation factor 15-pretreated MSCs (GDF15-MSCs) in enhancing cardiac repair following MI and to determine the underlying mechanisms. Methods MSCs with or without GDF15 pretreatment were exposed to serum deprivation and hypoxia (SD/H) challenge. Apoptosis of MSCs was assessed by TUNEL staining. The conditioned media (CM) of MSCs and GDF15-MSCs was collected by centrifugation. MSCs and GDF15-MSCs were transplanted into the peri-infarct region in a mouse model of MI. Cardiac function, fibrosis and MSC survival were examined 4 weeks after MSC transplantation. Results Pretreatment with GDF15 greatly reduced SD/H-induced apoptosis of MSCs via inhibition of reactive oxygen species (ROS) generation by attenuating mitochondrial fission. Mechanistically, GDF15 pretreatment ameliorated mitochondrial fission of MSCs under SD/H challenge by activating the AMPK pathway. These effects were partially abrogated by AMPK inhibitor. Pretreatment with GDF15 also promoted paracrine effects of MSCs in vitro, evidenced by improving tube formation of HUVECs, and inhibited the apoptosis of cardiomyocytes induced by SD/H. At 4 weeks after transplantation, compared with MSCs, GDF15 pretreatment strongly promoted the survival of MSCs in the ischemic heart with consequent enhanced cardiac function, reduced cardiac fibrosis and increased angiogenesis. Conclusions Our study showed that pretreatment with GDF15 promoted the cardioprotective effects of MSCs in MI via regulation of pro-survival signaling and paracrine actions. GDF15 pretreatment is an effective approach to enhance the therapeutic efficacy of MSCs in ischemic heart disease.